Optimistic narrative future visions: a communication tool for promoting sustainable (plastic) behavior - Neef, Nicolas E.; Fußwinkel, Selina; Roos, Claudine; Frank, Lilli; Shihepo, Kapandu; Richter, Isabell (Frontiers in Psychology, 2023)
Plastic pollution is a pressing global issue, necessitating a focus on consumer behavior to curb this problem at its source. To effectively promote sustainable practices, communication strategies that employ future visions have gained attention. This study examines the effects of a narrative video intervention depicting an optimistic future vision concerning single-use plastic bag consumption in South Africa, compared to a representation of the prevailing status quo. Using a preregistered within-subject design, we assess the psychological and emotional responses to two scenarios of which one is illustrating adaptive behaviors toward reduced plastic bag usage, and the other showcasing current consumption patterns. Parametric analyses revealed a shift in emotional states, characterized by a greater experience of positive emotions and a reduced experience of negative emotions following the exposure to the optimistic future scenario video, as compared to the status quo video. Moreover, engagement with the optimistic future scenario was associated with higher levels of perceived behavioral control and behavioral intentions. No significant changes were found regarding sense of responsibility. These findings point to the potential of optimistic future visions to influence individuals at psychological and emotional levels. This renders optimistic future vision communication as an effective tool for sustainable behavior change, particularly in relation to the sustainable use of plastic shopping bags.